Cell-penetrating peptides TAT and 8R functionalize P22 virus-like particles to enhance tissue distribution and retention in vivo - Su, Shibo; Shen, Xuegang; Shi, Xinqi; Li, Xin; Chen, Jin; Yang, Wei; Sun, Mingxia; Tang, Yan-Dong; Wang, Haiwei; Wang, Shujie; Cai, Xuehui; Lu, Yu; et al. (Frontiers in Veterinary Science, 2024)
Virus-like particles (VLPs) are used as nanocontainers for targeted drug, protein, and vaccine delivery. The phage P22 VLP is an ideal macromolecule delivery vehicle, as it has a large exterior surface area, which facilitates multivalent genetic and chemical modifications for cell recognition and penetration. Arginine-rich cell-penetrating peptides (CPPs) can increase cargo transport efficiency in vivo. However, studies on the tissue distribution and retention of P22 VLPs mediated by TAT and 8R are lacking. This study aimed to analyze the TAT and 8R effects on the P22 VLPs transport efficiency and tissue distribution both in vitro and in vivo. We used a prokaryotic system to prepare P22 VLP self-assembled particles and expressed TAT-or 8R-conjugated mCherry on the VLP capsid protein as model cargoes and revealed that the level of P22 VLP-mCherry penetrating the cell membrane was low. However, both TAT and 8R significantly promoted the cellular uptake efficiency of P22 VLPs in vitro, as well as enhanced the tissue accumulation and retention of P22 VLPs in vivo. At 24 h postinjection, TAT enhanced the tissue distribution and retention in the lung, whereas 8R could be better accumulation in brain. Thus, TAT was superior in terms of cellular uptake and tissue accumulation in the P22 VLPs delivery system. Understanding CPP biocompatibility and tissue retention will expand their potential applications in macromolecular cargo delivery.